Physiochemical, sensorial and rheological characteristics of puree developed from Kashmiri peaches: influence of sugar, KMS and storage conditions. Issue 8 (August 2021) - Wani, Shefali; Bakshi, Rayees Ahmad; Khan, Zakir S.; Fayaz, Shemilah; Muzaffar, Khalid; Dar, B.N.
Abstract: The present investigation was undertaken to develop puree from peaches and to study the effect of peel, sugar, KMS concentrations and storage conditions on the acidity, pH, total soluble solids, total sugar and rheological behavior of purees. Two types of Purees (Peeled and unpeeled) were prepared by adding sugar (10% and 15%) and KMS (100ppm, 200ppm, 300ppm). A decrease in viscosity with an increase in shear rate was observed. The developed purees were stored at refrigerated and ambient conditions for 45 days and were analyzed at 15 days interval. During the storage period, there was a change in Gʹ and Gʺand the changes in pH and TSS were observed. The highest decrease in Gʹ and Gʺ was observed in P1 and P0 at ambient storage. The overall organoleptic score of all samples was acceptable, however, the organoleptic score of the P7 at refrigerated conditions was highest. Abstract : Peach, Rheology, Sensory evaluation, Acidity, Syrup concentration